THE CONCEPT OF THE DEATH IN THE NONMIMESIS LYRIC - Деркачова, О. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article deals with the concept of the death. It determines as main concept in nonmimesis lyric. On the base of Vasyl Stus’ poetry it analyses the main features of it: nucleus, nuclear zone, zone of near and far periphery.